Ekstraksi Titanium Dioksida (TiO2) dari Pasir Besi Pantai Tembakak Pesisir Barat sebagai Nanopartikel dengan Metode Hidrometalurgi - Lisa Rahmawati; Sudibyo; Dian Septiani Pratama; Zipora Sembiring; Suharso Suharso; Tika Anggraeni; Sarwan Sarwan (Analit : Analytical and Environmental Chemistry, 2024)
The iron sand sample came from Tembakak Beach, Pesisir Barat Regency, was prepared and then analyzed using XRF, obtained an Fe content of 58.294%; Si 18.525%; Ti 8.775%; Al 6.785%; Ca 3.885%; K 1.624%, as well as minor elements with a content below 0.5%. Titanium dioxide (TiO2) can be obtained from ilmenite (FeTiO3), by hydrometallurgical extraction methods. The extraction results were analyzed using XRF, obtained TiO2 at varying concentrations of HCl 7 Îœ of 15.033%, HCl 9 Îœ of 16.367%, and HCl 12 Îœ of 17.421%. XRD characterization of TiO2 extraction results with variations in HCl concentration of 12 Îœ shows that TiO2 has a rutile crystal phase with a tetragonal crystal structure, and has a particle size of 33.92 nm so that the TiO2 particles obtained are nanoparticles that play an important role in technological and industrial development.